Study on the mechanism of cadmium chloride pollution accelerating skin tissue metabolism disorder, aging and inhibiting hair regeneration - Du, Weibin; Dong, Yi; Wang, Zhenwei; Yao, Sai; Wang, Meijiao; Ji, Jinjun; Ruan, Hongfeng; Quan, Renfu (Frontiers in Public Health, 2022)
Drinking water contaminated by Cd2+ is one of the main ways it enters the body. When the skin is contaminated by environmental Cd2+, the skin barrier is destroyed. However, how Cd2+ induces skin metabolic disorder, and senescence and affects hair regeneration is not completely understood. In this study, 18 C57BL/6 mice were divided into a control group, a Low-dose group, and a High-dose group with 6 mice in each group, given water and different concentrations of cadmium chloride respectively by gavage, once a day. After 1 month of intervention, the skin tissues of mice were collected for non-targeted metabolomics analysis, and the related proteins were detected by immunofluorescence assay. Non-targeted metabolomics analysis showed that there were 29 different metabolites in Control vs Low-dose group, mainly including lysophospholipids, fatty acids and bile acids. There were 39 differential metabolites in the Control vs High-dose group, in addition to the above compounds, there were more amino acid compounds, and most of the metabolites had a reduced response after administration. Immunofluorescence assay showed that the higher the concentration of cadmium chloride, the more obvious the cell inhibition and apoptosis, and the more significant the damage to hair follicle stem cells. Thus, the study indicates that cadmium chloride pollution can accelerate skin metabolism disorder, and senescence and inhibit hair regeneration.